Onsager-Symmetry Obeyed in Athermal Mesoscopic Systems: Two-Phase Flow in Porous Media - Winkler, Mathias; Gjennestad, Magnus Aa.; Bedeaux, Dick; Kjelstrup, Signe; Cabriolu, Raffaela; Hansen, Alex (Frontiers in Physics, 2020)
We compute the fluid flow time correlation functions of incompressible, immiscible two-phase flow in porous media using a 2D network model. Given a properly chosen representative elementary volume, the flow rate distributions are Gaussian, and the integrals of time correlation functions of the flows are found to converge to a finite value. The integrated cross-correlations become symmetric, obeying Onsager's reciprocal relations. These findings support the proposal of a non-equilibrium thermodynamic description for two-phase flow in porous media.